A two-dimensional mutate-and-map strategy for non-coding RNA structure - Kladwang, Wipapat; VanLang, Christopher C.; Cordero, Pablo; Das, Rhiju (Nature chemistry, 2011)
Non-coding RNAs fold into precise base-pairing patterns to carry out critical roles in genetic regulation and protein synthesis, but determining RNA structure remains difficult. Here, we show that coupling systematic mutagenesis with high-throughput chemical mapping enables accurate base-pair inference of domains from ribosomal RNA, ribozymes and riboswitches. For a six-RNA benchmark that has challenged previous chemical/computational methods, this ‘mutate-and-map’ strategy gives secondary structures that are in agreement with crystallography (helix error rates, 2%), including a blind test on a double-glycine riboswitch. Through modelling of partially ordered states, the method enables the first test of an interdomain helix-swap hypothesis for ligand-binding cooperativity in a glycine riboswitch. Finally, the data report on tertiary contacts within non-coding RNAs, and coupling to the Rosetta/FARFAR algorithm gives nucleotide-resolution three-dimensional models (helix root-mean-squared deviation, 5.7 Å) of an adenine riboswitch. These results establish a promising two-dimensional chemical strategy for inferring the secondary and tertiary structures that underlie non-coding RNA behaviour. Non-coding RNAs are ubiquitous biomolecules with intricate three-dimensional folds that are difficult to characterize. This Article presents an information-rich strategy for inferring RNA structure by combining nucleotide-by-nucleotide mutagenesis with single-nucleotide-resolution chemical mapping.